Teaching Foreign Languages with the Help of its Technology (Eurasian Scientific Herald, 2022)
The article reveals the process of using multimedia technologies and results in teaching foreign languages. Effective methods are analyzed that lead to a clear perception of information in a foreign language. This article also discusses a motivational approach for the effective achievement of the goal.